THEORETICAL AND TECHNOLOGICAL ASPECTS FOR CREATION OF ECONOMICALLY DOPED PROTECTIVE LAYERS MADE OF DIFFUSION AND DOPED ALLOYS - V. M. Konstantinov (Наука и техника)
The paper presents a developed methodological approach to obtaining economically doped protective layers and coatings made of diffusion and doped alloys. Metallic powders, wire, discrete chip waste serve as a raw material basis for obtaining the alloys. The developed theoretical and technological aspects of economically doped alloy synthesis have made it possible to work out a range of special protective layers and coatings for various operational conditions.